Konseling Sebaya Sebagai Pencegahan Perilaku Seksual Berisiko Pada Remaja - Sang Ayu Made Adyani; Wiwin Winarsih; Poppy Fitriyani (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2019)
Adolescent are a risk groups who have certain characteristics which has a contribution that can cause health problem, one of them is a risky sexual behavior. The aim of this research is to know the correlation of the utilization of peer counseling with risky sexual behavior in adolescent aggregate in South Jakarta. The design of correlation analysis with cross sectional method is used in this research to 108 respondent by simple random sampling. The result of this analysis chi square shown that there is a significant correlation of the utilization of peer counseling with risky sexual behavior in adolescent aggregate ( p value : 0,003). The results of this study serve as an input in improving nursing care to adolescent aggregate through peer counseling activities that pay more attention to the developmental needs of adolescents.